Les effets néfastes de la kubeia. Mise en jeu du prestige et de l’image sociale en Grèce classique - Marco Vespa (Pallas, 2020)
In several texts from classical antiquity, the invention of dice and board games is associated with attempts to put an end to crisis in the political community, as the stories about Palamedes seem to show. Beside the fictional context of mythical narratives the cultural value of dice and board games enters into other discursive representations. In particular, the speech of the rhetorician Alcidamas (On the Betrayal of Palamedes, fr. 2 Avezzù) in the 4th century BC invites us to analyse the dark side of board games, especially those that fell into the category of κυβεία, that is gambling activities. Different texts from classical Athens, from Herodotus to Cratinus, including Isocrates, use enunciative processes in order to devaluate these gambling activities and stigmatize citizens/soldiers and political élites. This article demonstrates how play has been one of the ways of building or disfiguring the social image of an individual within the civic community.